Metformin and phenformin deplete tricarboxylic acid cycle and glycolytic intermediates during cell transformation and NTPs in cancer stem cells - Janzer, Andreas (National Academy of Sciences, 2014)
Metformin, a first-line diabetes drug linked to cancer prevention in retrospective clinical analyses, inhibits cellular transformation and selectively kills breast cancer stem cells (CSCs). Although a few metabolic effects of metformin and the related biguanide phenformin have been investigated in established cancer cell lines, the global metabolic impact of biguanides during the process of neoplastic transformation and in CSCs is unknown. Here, we use LC/MS/MS metabolomics (>200 metabolites) to assess metabolic changes induced by metformin and phenformin in an Src-inducible model of cellular transformation and in mammosphere-derived breast CSCs. Although phenformin is the more potent biguanide in both systems, the metabolic profiles of these drugs are remarkably similar, although not identical. During the process of cellular transformation, biguanide treatment prevents the boost in glycolytic intermediates at a specific stage of the pathway and coordinately decreases tricarboxylic acid (TCA) cycle intermediates. In contrast, in breast CSCs, biguanides have a modest effect on glycolytic and TCA cycle intermediates, but they strongly deplete nucleotide triphosphates and may impede nucleotide synthesis. These metabolic profiles are consistent with the idea that biguanides inhibit mitochondrial complex 1, but they indicate that their metabolic effects differ depending on the stage of cellular transformation.